Potent antimicrobial activity of Rhizophora mucronata - Kusuma, S; Anil Kumar, P; Boopalan, Kamala (Journal of Ecobiotechnology, 2012)
The antimicrobial activity of n-hexane, chloroform and methanol extracts of leaves and roots of the plant Rhizophora mucronata were studied. Ampicillin and clotrimazole were used as standard antibacterial and antifungal agents respectively. The result of the study revealed that the n-hexane extract and chloroform extract of leaves exhibited strong inhibitory action against Bacillus subtilis, Staphylococcus aureus, Candida albicans, Aspergillus fumigatus and Aspergillus niger and moderate inhibitory action against Pseudomonas aeruginosa and Proteus vulgaris. The rest of the extracts showed good inhibitory activity.